The wife is nurtured in Islamic jurisprudence (Journal of the College of Basic Education, 2020)
Praise be to God, who permitted marriage and prohibited incest, and permitted this nation unless it was permitted by others, and peace and blessings be upon the envoy as a mercy to the worlds, our master, the Messenger of God, Muhammad bin Abdullah, the sincere prophet, the faithful promise, and his good and pure family, and his righteous companions, and everyone who followed his gift And victory of his year, until the Day of Judgment.And now: God الله legalized marriage and permitted it to build a family that is based on mercy and affection. The Almighty said: (And among his signs is that He created for you wives from yourselves to live in and make among you affection and mercy. There are signs for people among them to think) (), and when the family is the basis of society, and if The disintegration of society as a whole disintegrated and deviated from the divine approach that God wanted  for him, so Islam has organized marital life in an organization that is not matched by an organization, and guides me to everything that fixes it, and makes each of the spouses a role and a job to perform, and when the roles are mixed, and each of them goes out of his job and role To perform the function of the other, and he is not prepared for this function For the family of confusion, obstruction, and ruin. This creates a division between the spouses and the displacement of their children.The importance of the topic: Our topic tagged (the disbelief of the wife in Islamic jurisprudence) is one of the sensitive issues that destroy the family entity and which has spread in our societies. This research deals with an important social issue, which many families suffer from, and this is due to ignorance of the Sharia and the nature related to it. The relationship between the couple and the lack of awareness of the role of the family and its importance in building society, so it is necessary to clarify the legal provisions of this issue (the disbelief of the wife) by mentioning the opinions of scholars and their reasoning in this vital issue. Reasons for choosing a topic: To choose a topic for a wife’s disbelief, there are many reasons, the most important of which are:1. The importance of the family in building society, forming its interconnected fabric, and contributing to clarifying an important aspect of its legal provisions, which regulate family relations in it.2. The disbelief of the wife has a great impact on destabilizing the family entity and may destroy it, so it was necessary to highlight it, a statement and rulings.3. This study puts in the hands of the Muslim family clear marks, and broad lines of the relationship between the spouses, as it draws for them the most important sound foundations for building a strong marital relationship, based on love, affection, responsibility, and mutual respect4. I invite my brothers, researchers, to address this issue in terms of jurisprudence, in a comprehensive, in-depth manner that deals with the provisions of Sharia in it, a contemporary jurisprudential study that takes into account the reality of people and the sensitivity of the topic.5. Perhaps it would be a blessed step on the path to building happy homes, in order to be full of love, goodness, and affection, in the shadows of the Qur’an and the law of the one and the same religion.Research methodology: As for the method followed, it is a descriptive, inductive approach, in which I touched upon this subject in a simple and succinct manner, through presenting the opinions and doctrines of the jurists, and clarifying their evidence and comparing them, which helps in understanding and disturbing what has occurred, and has not been a problem that has not been affected by the problem and the disturbance of it. The research method is summarized in the following matters:1. Refer to the main and authentic sources relevant to the topic of research, from the books of interpretation, hadith, and Islamic jurisprudence,2. Attributing the verses to their walls, based on the Holy Qur’an.3. Graduating the hadiths from the noble hadiths from their manifestations. If they appear in the two Sahihs, then I will be satisfied with that, otherwise, I search for them in the other hadith books.4.. I put a conclusion to the research that included my most important results through the researchResearch plan: For the research requirements, I divided this research into two studies after the introduction, which included: the importance of the topic, the reasons for choosing it, its methodology, and its plan, as follows:The first topic: The concept of a wife’s disbelief and its manifestations, and it has two requirements: The first: defines the wife’s disbelief by language and terminology. The second requirement: the rule of the wife’s disbelief and its evidence, and its effects. Anju and the conclusion came to include the most important results that were reached through the research, and then mentioned the sources and referencesPraise be to God, whose grace is righteous, and may God’s prayers and peace be upon the Messenger of God, his family and companions, and from his parents, and follow his guidance